Approximation properties and q-statistical convergence of Stancu-type generalized Baskakov-Szász operators - Cai, Qing-Bo; Kilicman, Adem; Mursaleen, Mohammad Ayman (Hindawi, 2022)
In this article, we introduce Stancu-type modification of generalized Baskakov-Szász operators. We obtain recurrence relations to calculate moments for these new operators. We study several approximation properties and q-statistical approximation for these operators.